Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 262 species occurrences available in GBIF matching the query: { "and" : [ "Country is Mexico", "Geometry POLYGON((-99.810791 26.138179,-99.810791 26.034574,-99.567718 26.034574,-99.567718 26.138179,-99.810791 26.138179))" ] } The dataset includes 262 records from 17 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0006902-150615163101818/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences